Development of Visual-Based Interactive Media to Understand the Water Cycle in Elementary Schools - Mufidah, Farah Salma; Mustoip, Sofyan; Janan, Nabila (EduBase : Journal of Basic Education, 2024)
This research aims to develop visual-based interactive media that is effective in increasing elementary school students' understanding of the concept of the water cycle. The water cycle is an important material in the science curriculum, but it is often difficult for students to understand because of its abstract nature. This research uses a qualitative approach with the research and development (R&D) model ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of teachers and fourth grade students in one of the elementary schools in Indonesia. Data was collected through observation, in-depth interviews and documentation, then analyzed thematically. The research results show that visual-based interactive media, such as animation and digital illustrations accompanied by interactive narratives, can significantly increase students' understanding of the concept of the water cycle. This media also increases student participation in the learning process and helps teachers convey material in a more interesting way. Using this media makes it easier for students to connect theoretical concepts with everyday phenomena, such as rain and evaporation. The teacher stated that this media was practical to use and relevant to learning needs. In conclusion, visual-based interactive media can be an innovative solution in increasing the effectiveness of learning water cycle concepts in elementary schools. This research recommends further development for widespread integration of technology in science learning.